Moderately dilated ascending aorta—The right wrap?. Issue 4 (27th January 2022) - Narayan, Pradeep; Doddamane, Aditya N.; Bryan, Alan J.
Abstract: External reinforcement of the dilated or thin‐walled aorta has been tried for nearly half a century. A range of materials has been used as external support. This commentary assesses the evidence that exists regarding the efficacy of wrapping the aorta as well as compares the different options available with a particular focus on the usage of the autologous pericardium.